2016
DOI: 10.1111/jcpe.12491
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of periapical radiography in assessing bone level in implants affected by peri‐implantitis: a cross‐sectional study

Abstract: The intra-operatively measured peri-implant bone levels were more apical than the radiographic bone levels. The intra-operatively assessed peri-implant bone levels (SurgBL) were similar at all the circumferential positions around the implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 34 publications
5
63
2
3
Order By: Relevance
“…(2017) concluded that probing depth around peri‐implantitis affected implants significantly underestimated the true bone level by 1 mm. Garcia‐Garcia, Mir‐Mari, Benic, Figueiredo and Valmaseda‐Castellon (2016) showed a significant underestimation of the interproximal bone level by intra‐oral radiography of 1.3 mm on average. Merli et al.…”
Section: Discussionmentioning
confidence: 97%
“…(2017) concluded that probing depth around peri‐implantitis affected implants significantly underestimated the true bone level by 1 mm. Garcia‐Garcia, Mir‐Mari, Benic, Figueiredo and Valmaseda‐Castellon (2016) showed a significant underestimation of the interproximal bone level by intra‐oral radiography of 1.3 mm on average. Merli et al.…”
Section: Discussionmentioning
confidence: 97%
“…16 Digital intraoral radiographs were taken using the long-cone paralleling technique. To prepare parallel radiographs, a film holder (Dentsply Rinn, PA, USA) was used to standardize the angulation between the X-ray beam and the film.…”
Section: Peri-implant Bone Lossmentioning
confidence: 99%
“…Guided bone regeneration (GBR) is a predictable technique for augmenting the alveolar ridge width that has been used for more than two decades, and osseointegration and long-term implant survival rate have been reported to be similar in grafted areas than in native bone [4, 5]. …”
Section: Introductionmentioning
confidence: 99%